Metode Drill Pada Pembelajaran PIP Gitar Elektrik Di SMK Negeri 7 Padang - Agusnadi, Angga; Irdhan Epria Darma Putra (Universitas Negeri Padang, 2024)
This study aims to describe the application of the drill method in learning the Main Instrument Practice (PIP) of electric guitar for class XI students at SMKN 7 Padang. The research method used is a descriptive research method that focuses on the drill method in learning PIP electric guitar at SMKN 7 Padang. The results of this study make students focus, actively practice, and get the opportunity to correct mistakes with direct guidance from the teacher using the drill method. This method allows teachers to monitor student development directly, so that the learning process becomes more focused. During learning, students showed a high enthusiasm for learning, which not only improved their guitar playing skills but also created an active and dynamic classroom atmosphere. Teaching and learning activities ran smoothly, triggering student enthusiasm in following the lesson. The use of fingering, picking, and pentatonic scale technique materials is very appropriate, because this material is the basis for playing electric guitar well and correctly. By learning these basic techniques, students will understand the basic techniques of playing electric guitar and can improve their individual abilities.